EVALUASI PELAKSANAAN PROGRAM UPAYA KESEHATAN JIWA DI PUSKESMAS BANDARHARJO KOTA SEMARANG TAHUN 2018 - Jessica Masta Hothasian; Chriswardani Suryawati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The relapse rates of mental disorder in Central Java in 2018 have reached 2,2% per 1.000 population. Bandarharjo Primary Health Center (Puskesmas) itself was a health center with the highest mental health cases in Semarang. The objective of this research was to evaluate the Mental Health Program implementation in the work areas of Bandarharjo Primary Health Center. The research design is qualitative with a descriptive analytic approach. Data was collected from in-depth interviews and observations based on purposive sampling criteria. Subjects in the study consisted of two executive doctors, a coordinator in Mental Health Program, and a nurse. These four subjects were categorized as the main informant. Representatives from mental disorder patient's family and health cadres were included as well to be part of triangulation informants. The results, the implementation of mental health program in Bandarharjo Primary Health Center had not been optimal. This was because the number of patients with severe mental disorder, who received mental health services according to standard were only 94.7%. Therefore, there were still about 5.3% patients who had not received mental health services. The was a lacking in Standard Operation Procedures (SOP) for each stages of program implementation, especially the initial management stage (drug administration) and socialization regarding Mental Health Program. It is better to improve the socialization and promotion of Mental Health Program in Bandarharjo Primary Health Center. There needs to be an improvement in the distribution system of medicines from the City Health Office to the Puskesmas so that there are no delays as well as a review of the latest BPJS rules related to the tiered referral system which is still a problem in the field.